Dinamika Pemekaran Nagari di Kabupaten Solok Selatan: Studi Kasus Nagari Lubuk Gadang Selatan, Kecamatan Sangir, Kabupaten Solok Selatan Tahun 2007-2021 - Ilham Fahiza Putra; Syafrizal Syafrizal; Armansyah Armansyah (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
The article aims to explore the governance, social, and economic dynamics resulting from the division into Nagari Lubuk Gadang Barat Daya and Nagari Lubuk Gadang Barat. The research scope spans from 2007 when Nagari Lubuk Gadang was formed until 2021 when it was divided. The study employs a historical research method comprising topic selection, source collection, source criticism, interpretation, and historiography. Nagari Lubuk Gadang Selatan, located in Sangir Subdistrict, South Solok Regency, West Sumatra Province, comprises 15 jorongs. It was established in 2007 to meet the community's demands for independent fund management. Due to population growth and the increasing number of jorongs, Nagari Lubuk Gadang Selatan was divided into two new nagaris from 2017 onwards. The expansion aims to ensure equitable development and access to village funds for the community's prosperity.